2022
DOI: 10.1186/s12958-022-00905-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, perinatal and childhood outcomes in women with and without polycystic ovary syndrome and metformin during pregnancy: a nationwide population-based study

Abstract: Background Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that affects women in reproductive age and represents an unfavourable risk factor for several pregnancy and perinatal outcomes. Despite, no guidelines or pharmaceutical strategies for treating PCOS during pregnancy are available. The aim of this study is to determine the association between polycystic ovary syndrome with or without metformin and the pregnancy, perinatal outcomes as well as the risk of obesity in children born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 69 publications
1
30
0
2
Order By: Relevance
“…In prospective clinical trials in obese non-diabetic women, metformin use versus placebo did not alter the risk of LGA birth, 19 20 whereas in a recent cohort study on pregnant women without diabetes and PCOS exposed or non-exposed to metformin, a reduced LGA risk for metformin exposure was found. 21 Prepregnancy BMI and gestational hyperglycemia are considered drivers of LGA risk in the offspring. 22 In summary, current evidence suggests that metformin may reduce hyperglycemia-related LGA.…”
Section: Discussionmentioning
confidence: 99%
“…In prospective clinical trials in obese non-diabetic women, metformin use versus placebo did not alter the risk of LGA birth, 19 20 whereas in a recent cohort study on pregnant women without diabetes and PCOS exposed or non-exposed to metformin, a reduced LGA risk for metformin exposure was found. 21 Prepregnancy BMI and gestational hyperglycemia are considered drivers of LGA risk in the offspring. 22 In summary, current evidence suggests that metformin may reduce hyperglycemia-related LGA.…”
Section: Discussionmentioning
confidence: 99%
“…Fornes et al [41 ▪ ] also found an increased risk of obesity in offspring of individuals with PCOS not treated with metformin, as well as in individuals without PCOS treated with metformin compared with those without PCOS or metformin treatment. Individuals with PCOS on metformin during pregnancy had no increased risk of childhood obesity [41 ▪ ]. There was no increased risk of adverse outcomes in pregnant individuals with PCOS on metformin compared with those without PCOS or metformin treatment [41 ▪ ].…”
Section: Metformin For Polycystic Ovarian Syndrome In Pregnancymentioning
confidence: 92%
“…Individuals with PCOS on metformin during pregnancy had no increased risk of childhood obesity [41 ▪ ]. There was no increased risk of adverse outcomes in pregnant individuals with PCOS on metformin compared with those without PCOS or metformin treatment [41 ▪ ]. Further research is warranted into the effect of PCOS and metformin during pregnancy on offspring.…”
Section: Metformin For Polycystic Ovarian Syndrome In Pregnancymentioning
confidence: 98%
“…Indeed, metformin administration in STZ-diabetic rats resulted in improved testosterone, LH and FSH hormones levels (Nasrolahi et al 2013 ). Various studies have shown that treatment with metformin is effective in reproductive system diseases, including female and male reproduction in endocrine pathologies (Lee et al 2019 ; Shpakov 2021 , ul haq Shah, Shrivastava et al 2022 ), endometriosis (Zhao et al 2018 , Mu et al 2020 , Stochino-Loi et al 2021 , Kimber-Trojnar et al 2022 ), polycystic ovary syndrome (Chen et al 2019 ; Fornes et al 2022 , Xu et al 2022 ) and prostate (Sun et al 2018 , Chen, Wang et al 2021a , b , c , Aydın et al 2022 , Morale et al 2022 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%